Model Optimisasi untuk Penjadwalan Ulang Perjalanan Kereta Api - Suprayogi Suprayogi; Hery Ramdhani (Jurnal Teknik Industri, 2015)
This paper discusses the train rescheduling problem due to disturbances. The train rescheduling problem discussed in this paper is taken from a real train network of DAOP II Bandung in Jawa, Indonesia. The train network consists of block sections including unidirectional double-tracks and bidirectional single-tracks. There are some connections among trains because they use same rolling stocks. A mixed integer linear programming model is formulated to represent the problem. Main decision variables of the model are new departure and arrival times due to the disturbance. The objective function to be minimized is the total weighted delay. The model is examined using a hypothetical instance for four disturbance cases. Numerical experiments show that the model can represent the problem under study